2001
DOI: 10.1046/j.1525-1594.2001.06792.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Extracorporeal Life Support for Treatment of Fatal Mechanical Complications Associated with Acute Myocardial Infarction

Abstract: Mechanical complications of acute myocardial infarction (AMI), such as free wall rupture, ventricular septal perforation (VSP), and mitral regurgitation due to papillary muscle rupture, are associated with high mortality rates. These complications result in extreme deterioration and increased risk of death in patients who do not receive timely resuscitation and surgical treatment. We studied the effectiveness of percutaneous extracorporeal life support (ECLS) for fatal mechanical AMI complications. Nine patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Most of the patients in these studies were of heterogeneous aetiologies of cardiopulmonary diseases 9 11 13–15. Some of them evaluated the role of ECPR in patients with cardiogenic shock,16–18 but only few of them suggested that ECPR may promote survival for patients with AMI 5 19 20. Our study confirmed that cardiac arrest patients from AMI can benefit from ECPR.…”
Section: Discussionsupporting
confidence: 79%
“…Most of the patients in these studies were of heterogeneous aetiologies of cardiopulmonary diseases 9 11 13–15. Some of them evaluated the role of ECPR in patients with cardiogenic shock,16–18 but only few of them suggested that ECPR may promote survival for patients with AMI 5 19 20. Our study confirmed that cardiac arrest patients from AMI can benefit from ECPR.…”
Section: Discussionsupporting
confidence: 79%
“…Even if European and American guidelines recommend VA-ECMO use in case of ACS leading to heart failure refractory to medical treatment, with IIa and IIb proof levels respectively [61,62], to our knowledge, no randomized study has ever reported any benefit of VA-ECMO as compared to medical treatment alone. These guidelines are only supported by results from observational series [3,[63][64][65]. Indeed, a historical case-control study published in 2010 reported a benefit of VA-ECMO on 30-day survival (OR = 0.22 ; 95%CI [0.06-0.80] ) in 71 patients with profound cardiogenic shock and acute coronary syndrome [65].…”
Section: Acute Coronary Syndrome (Acs)mentioning
confidence: 99%
“…The decision as to whether deferring is feasible or not should be based on the haemodynamic stability of the patient. Patients will typically be treated with supportive medication, an intra-aortic balloon pump (IABP) and/or mechanical circulatory support (MSC) [11, 15]. …”
Section: Interval Between Diagnosis and Occlusionmentioning
confidence: 99%